MicroRNA Regulation of Host Immune Responses following Fungal Exposure - Croston, Tara L.; Lemons, Angela R.; Beezhold, Donald H.; Green, Brett J. (Frontiers in Immunology, 2018)
Fungal bioaerosols are ubiquitous in the environment and human exposure can result in a variety of health effects ranging from systemic, subcutaneous and cutaneous infections to respiratory morbidity including allergy, asthma, and hypersensitivity pneumonitis. Recent research has focused on the role of microRNAs (miRNAs) following fungal exposure and are an overlooked, yet important, group of regulators capable of influencing fungal immune responses through a variety of cellular mechanisms. These small noncoding RNAs function to regulate gene expression at the post-transcriptional level and have been shown to participate in multiple disease pathways including cancer, heart disease, apoptosis, as well as immune responses to microbial hazards and occupational allergens. Recent animal model studies have characterized miRNAs following exposure to inflammatory stimuli. Studies focused on microbial exposure, including bacterial infections, as well as exposure to different allergens have shown miRNAs, such as miR-21, miR-146, miR-132, miR-155 and the let-7 family members, to be involved in immune and inflammatory responses. Interestingly, the few studies that have assessed the miRNA profiles following fungal exposure have identified the same critical miRNAs that have been characterized in other inflammatory-mediated and allergy-induced experimental models. Review of available in vitro, animal and human studies of exposures to Aspergillus fumigatus, Candida albicans, Cryptococcus neoformans, Paracoccidioides brasiliensis, and Stachybotrys chartarum identified several miRNAs that were shared between responses to these species including miR-125 a/b (macrophage polarization/activation), miR-132 (TLR2 mediated signaling), miR-146a (TLR mediated signaling, alternative macrophage activation), and miR-29a/b (natural killer cell function, C-leptin signaling, inhibition of Th1 immune response). Although these datasets provide preliminary insight into the role of miRNAs in fungal exposed models, interpretation of miRNA datasets can be challenging for researchers. To assist in navigating this rapidly evolving field, the aim of this review is to describe miRNAs in the framework of host recognition mechanisms and provide initial insight into the regulatory pathways in response to fungal exposure.